Neutrophil extracellular traps induce a hypercoagulable state in glioma - Shihua Zhang; Mengfan Guo; Qianzi Liu; Jingfeng Liu; Yankun Cui (Immunity, Inflammation and Disease)
Abstract Background Venous thromboembolism (VTE) is one of the leading complications in glioma patients. Neutrophil extracellular traps (NETs) have been reported to play a critical role in the physiopathology of cancer. We aimed to investigate the presence and potential role of NETs in the hypercoagulable state in glioma patients. Moreover, we evaluated the interaction between NETs and endothelial cells (ECs) in glioma patients. Methods The plasma levels of NETs were detected by enzyme‐linked immunosorbent assay. The NET procoagulant activity was performed based on fibrin formation assays. The NET generation and NET‐treated ECs in vitro were observed by confocal microscopy. Activated platelets (PLTs) and PLT‐neutrophil aggregates were detected by flow cytometry. Results Plasma NET markers were significantly higher in stage III/IV glioma patients than in stage I/II glioma patients and healthy subjects. PLTs from glioma patients tended to induce NET formation than those from healthy subjects. NETs contributed to the hypercoagulable state in glioma patients. After ECs were incubated with NETs isolated from stage III/IV glioma patients, they lost their intercellular connections and were converted into procoagulant phenotypes. Combining DNase I and activated protein C markedly decreased endothelial dysfunction. Conclusions Our results showed the interaction between NETs and hypercoagulability in glioma patients. Targeting NETs may be a potential therapeutic and prevention direction for thrombotic complications in glioma patients.